Optimization of Business Processes Based on the Supply Chain Management in an Accounting Department - A.Z Kintonova; M.A Yermaganbetova; G.M Abildinovaa; N.N Ospanova; Z.K Abdugulova; N.S Glazyrina (International Journal of Supply Chain Management, 2019)
Modeling and automation of business processes are key to the successful company’s operation. Enterprise prosperity depends on professional modeling of business processes by considering the supply chain management. The urgency of the work consists of the real need to optimize the business process of the accounting department. The chapter describes the following aspects: the methodology for modeling business processes of the accounting department in an enterprise; results of technologies analysis and business processes models; business processes of fixed assets, planning and accounting documents of the enter- prise’s accounting department. The chapter reflects the methodology for accounting for fixed assets, determines the procedure for working with fixed assets of the enterprise, discloses information on fixed assets in the financial statements of the enterprise, and describes the target model of accounting process for fixed assets, on the base of that further automation of this process is planned. Moreover, the work represents the resultsofbusinessprocessesoptimizationofenterprise’sfixedassetsaccounting, measures to reduce the processing time of accounting information ,as well as methods for eliminating bureaucratic procedures inworkorganizationwithfixedassets.Optimizationoffixedassetsaccountinginvolvestheintroduction of the following target processes in the enterprise.